ASSUMPTIONS FOR OPTIMIZATION OF ANDRAGOGIC INTERACTION:METHODOLOGICAL AND PRACTICAL GROUNDING - Jurate Adomaitiene; Ilona Zubrickiene (European Scientific Journal, ESJ, 2014)
The article analyses links between personal (individual) independence (autonomy), interpersonal dependence and andragogic interaction, also optimization of these links by grounding their methodological and practical assumptions. The methodological basis rests on stimulus-response theory, assisting in spotlighting of assumptions for transformation of personal (individual) independence into interpersonal dependence, significance of interpersonal dependence and reliance on optimization of andragogic interaction. Comparative analysis of results in 2001 and 2011 research, revealing positive and negative experience of learners in teamwork and project activity was invoked. Theoretical and empiric insights of the article can be helpful for andragogues/lecturers and administrators of adult education institutions, for all those working with adults and striving for qualitative changes in andragogic interaction.